A Reliability Analysis Of Supercapacitor Energy Storage In Multi Engine Unlimited Bus Systems Using The Critical Paths Method - Ika Ayu Wandira; Solly Aryza; Amani Darma Tarigan (Jurnal Scientia, 2024)
In modern industry, industrial revolution 4.0, energy storage systems are becoming increasingly important to support reliable and efficient performance. One of the technologies used in energy storage systems is supercapacitors. where Supercapacitors offer advantages in terms of high energy charging and discharging speeds, long service life, and the ability to withstand extreme temperatures. One of the characteristics of this power plant is the instability of the power released by this plant due to varying wind speeds. One solution to overcome this is to add energy storage to the generating system which works as power smoothing so that the power sent to the load can be maintained constant. This system can work as an energy store when the power released by the generator exceeds the power required by the load and can be an energy source when the power released by the generator is less than the power required by the load. The problem with energy storage in general is that the usage cycle tends to be low. Supercapacitors, with their characteristics of high power density, high efficiency and high usage cycles, are considered capable of overcoming the problems of other energy storage systems. This final project contains a study of the use of supercapacitors as energy storage in wind power plants, with a focus on comparing several parameters of supercapacitors with lead acid batteries. Based on the simulation results in this research, it can be concluded that supercapacitors have a power density and number of life cycles that tend to be higher than batteries, but have disadvantages, including a small energy capacity and relatively more expensive costs compared to batteries. Supercapacitors can also work as power smoothers to keep power on the DC link constant.